Apraxia of Speech : A Phonologic or Motoric Disorder ? - Gopal H.S; Mirelli Brogli (Journal of All India Institute of Speech and Hearing, 1990)
Apraxia of speech has been considered as a phonologic disorder by some researchers and as a motoric disorder by others, and the debate continues. The current study attempted to further explore this issue using acoustic analysis of speech segments. Acoustic durations of high and low vowels were obtained from two apraxics and two normal speakers at two speaking rates and in two postvocalic consonantal voicing contexts. The results of the study showed that the apraxics had abnormally long vowel durations; failed to maintain a significant duration difference between high and low vowels; did not vary speaking rate and had poor motor precision. However, they did manifest longer vowel durations when followed by a voiced postvocalic consonant. These findings were used to infer that apraxia of speech is primarily a motoric disorder with an intact phonological system.